Soil properties and methane cycling gene abundances in the foreland soil on the Tibetan Plateau - Tingting Xing (PANGAEA, 2022)
Glacier foreland soil flooded by melt water annually during the melting season, altering soil water content or other soil properties. We collected soil samples in the Longxiazailongba Glacier foreland on the Tibetan Plateau in August 2017. Measuring the soil pH, moisture, Ammonium nitrogen (NH4+), Nitrate nitrogen (NO3-), Total Nitrogen (TN), Organic matter (OM), Available phosphorus (AP). Soils were neutral to slight alkaline, and pH of hollows were significantly higher than those in hummock soils. In contrast, available phosphorous was significantly higher in hummock soils than in hollow soils. Besides, we also quanified mcrA and pmoA gene abundances. With measuring methane fluxes in June (pre-melting season) and August (melting season) 2020, we also measured the soil moisture and pH. The results indicate that soil moisture was significantly higher in melting season (August) than in pre-melting season (June).